Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-03-02T14:31:54+01:00
A)
8/√5 - 1 = 8 * (√5 + 1) / (√5 - 1)(√5 + 1) = 8 * (√5 + 1) / 5 - 1 = 8 * (√5 + 1) / 4 = 2 * (√5 + 1) = 2√5 + 2

b)
√2 / √2 + 1 = √2(√2 - 1) / (√2 + 1)(√2 - 1) = 2 - √2 / 2 - 1 = 2 - √2 / 1 = 2 - √2

c)
√7 + 2 / √7 - 2 = (√7 + 2)(√7 + 2) / (√7 - 2)(√7 + 2) = 7 + 2√7 + 2√7 + 4 / 7 - 4 = 4√7 + 11 / 3
2010-03-02T14:34:13+01:00
A)8/√5-1 = 8/√5-1 * √5+1/√5+1= 8√5+8/5-1= 8√5+8/4= 2√5+2
b)√2/√2+1 = √2/√2+1 * √2-1/√2-1 = 2-√2/2-1 = 2-√2/1 = 2-√2
c)√7+2/√7-2 = √7+2/√7-2 * √7+2/√7+2= 11+4√7/7-4=11+4√7/3

Pozdrawiam.